Strategic behavior of e-commerce businesses in online industry of electronics from a customer perspective - Zuzana Svobodová; Jaroslava Rajchlová (Administrative Sciences, 2020)
The issue of online shopping behavior is gaining importance with the continued development of e-commerce. E-commerce businesses that aim to be successful in the online market in the long run must consider the factors of online shopping behavior when creating and implementing their e-commerce strategy. This paper is focused on the strategic behavior of e-commerce from a perspective of the online customer. The aim of the paper is to evaluate the strategic position of e-commerce businesses that focus on online sales of electronics, based on their strategic behavior from the customer's perspective. The first objective is to identify the current factors of online shopping behavior in the industry of online electronics. The second obejctive is to identify the current economic performance and financial strategy of e-commerce businesses and their relevance to strategic behavior in e-commerce. The third objective is to identify the possible differences in strategic behavior of e-commerce SMEs and e-commerce large businesses. The research methods employed were: situation analysis, benchmarking, quantitative research, selected methods of financial analysis. The selected methods of statistical induction were chosen to verify the research hypotheses. A research sample of 89 e-commerce businesses selling online electronics was selected for this research. It was found that most e-commerce businesses apply a balanced e-strategy based on the assessed factors of online shopping behavior that does not correspond to the progressive growth of e-commerce. Fifteen factors were identified that influence customers when choosing and buying electronics online. It was also found that the strategic behavior of e-commerce businesses is influenced by factors of online shopping behavior. Finally, it was found that the current balanced e-strategy of e-commerce businesses does not correspond with conservative financial strategy.
Keywords: 350; e-commerce; e-strategy; customer perspective; strategic behavior; online shoppingbehavior; electronics